ChemInform Abstract: Trifluorination of Sulfides and Dithioketals Using IF5‐Pyridine‐HF. Issue 32 (22nd July 2016) - Inoue, Toshiya; Nakabo, Sho; Hara, Shoji
Abstract: The stable fluorination reagent is used for the trifluorination of aryl alkyl sulfides with concomitant migration of the arylsulfanyl group.